Pendidikan Islam Dalam Karya Sastra (Telaah Kritis Atas Buku La Tahzan Karya ‘Aidh Al-Qarni Perspektif Filsafat Pendidikan Islam) - Lusia Mumtahana (Akademika, 2020)
The world of education in Indonesia indeed faces very complex problems and requires careful reform. To realize quality and efficient education, it is necessary to arrange and implement educational programs that are able to educate students in a sustainable manner. In this case the values of Islamic education are needed to improve the standard of living through all its aspects, which may not be able to reach the intended goals without going through a step-by-step process. By choosing the book titlled la tahzan as a scientific writing because in it the writer found the values of Islamic education that are absolutely needed in dealing with such problems. This is a library research and is a qualitative one. Data sources are then analyzed and the results are recorded and classified in accordance with the planned framework. The results of this study are: 1). to find out the values of Islamic education in the perspectives of education experts which include the value of religious education (aqidah islamiyah), the value of health education, the value of religious education, the value of sex education. 2). To find out the values of Islamic education in the book of Tahzan written by 'Aidh Al-qarni that includes both divine and human values. 3). to find out the differences and similarities of the values of Islamic education in the perspectives of education experts with the values of Islamic education in the book.